The Democratic Republic of the Congo: quantifying the crisis (World Health Organization, 2009)
While engaged in relief efforts in the war-ravaged Democratic Republic of the Congo, the World Health Organization is also focusing efforts on data collection and analysis of the rapidly changing situation as a basis for future humanitarian support. Fiona Fleck reports.